Social Networks Integration with Amadeus Affinity Shopper - Liljekvist, Anne-Marie (My University, 2010)
The purpose of this master thesis was to develop a prototype for a web application that integrates social features with the act of booking. Two platforms were chosen for this thesis, Facebook and Amadeus Affinity Shopper (Affinity). The prototype’s main goal was to demonstrate a usable interface with underlying communication to Facebook. The web application came to be called FBAffinity. A pre-study was dedicated to investigating the areas of social networks, Affinity and the technical issues. Functional requirements were gathered from Amadeus’ organization, mainly from marketing and development representatives. A user study was conducted mainly focusing on a cross section analysis of the users of Facebook and Affinity to determine the needs and requirements of FBAffinity users. A low-fidelity prototype was then developed to further gather user requirements from end-users in interviews about the initial design. High-fidelity prototypes were developed based on user input and changes of requirements from marketing and development division. The prototype was evaluated in two evaluation sessions with end-users and in one with expert representatives from MKT and DEV. The result of the 6-month thesis was in the form of an external Facebook web application using Flex, JavaScript, PHP and HTML. The focus lied within the keywords friends, sharing and reviews. A analysis of the evaluation results suggested that further work needs to be put in the prototype in terms of focus on entertaining the user and add more functionality.
Keywords: Information Technology; Informationsteknik